Developing the Attitude of Contentment (Qonaah) to Avoid Consumerism in the Era of Self-Reward (Journal Intellectual Sufism Research (JISR), 2024)
The phenomenon of self-reward has become increasingly prevalent in modern life, which tends to be materialistic and often drives excessive consumer behavior. This concept, initially intended to reward oneself after achieving certain goals, can become a justification for a consumerist lifestyle where happiness is measured by material possessions. In a modern era filled with social pressures and consumerist temptations, the attitude of qonaah, or contentment with what one has, becomes an essential solution. Qonaah helps individuals manage excessive desires, reduce stress, and maintain financial balance while fostering gratitude and simplicity. From a spiritual perspective, qonaah strengthens one's relationship with God and brings deeper inner peace. Additionally, the Sufi approach, which teaches qonaah, plays a key role in avoiding dependency on material things and cultivating spiritual well-being. In the context of psychotherapy, developing the attitude of qonaah also has a positive impact on mental health by reducing social pressures and enhancing life satisfaction. This journal aims to examine how the attitude of qonaah can be applied as an effective strategy in overcoming excessive consumer behavior, especially in the era of self-reward, through a combination of Sufism and psychotherapy.